Proposal of a SMEs Forecast Management Support System - Marin ANDREICA; Mădălina Ecaterina POPESCU; Dragos MICU (Revista de Management Comparat International)
This paper describes the main findings of the authors’ research concerning the conceptual aspects, the architecture and the functionality of a proposed SMEs forecast management support system, with customization on projected production management. The proposed system was experienced in SMEs industrial activity and is based on the concept of procedural modelling. Thus, it aims to assist the decision makers in elaborating forecasts and business planning in SMEs. Planning models are based on flexible optimization methods with vague restrictions and objective functions. The forecast activity is assisted by procedural models required to simulate several structures of indicators in order to forecast the evolution of the medium and long term synthetic indicators.